Sistema web para mejorar el proceso de registro de la información vehicular en la Unidad de Tránsito de la Municipalidad Provincial de San Martín - Arce Arbildo, Yerson (2014)
The Sub Division for the Welfare of Urban Transportation, Traffic and Road Safety Unit also known as Traffic is the specialist of the Provincial Municipality of San Martín, on the subject of transporting small vehicles in the city of Tarapoto and the province of San office Martin in the San Martín region. This Sub Management is currently getting a lot of requests (files) enabling vehicular freight and passenger transport, which are mandatory requirements according to Supreme Decree No. 055-2010-MTC and Municipal Ordinance No. 053- 2011-A / MPSM. Vehicular ratings are revalidated annually, which, along with the increasing number of vehicle units is producing a lot of information so it makes use of technologies for recording, storing and retrieval of this information indispensable. In this research proposes as a solution to systematize the process of vehicle registration information, to improve the process in the Sub Division for the Welfare of Urban Transportation, Traffic and Road Safety. This solution is designed as a bespoke system so the analysis, design and implementation of the organizational reality of that area spanned the SHV system is named for the acronym of (Enabling Traffic System) at the end of this report is implemented and fully functional in all modules covered whereby the benefits of its implementation became apparent. One of the greatest achievements of this research and its application of the solution was to reduce the time it takes to process an application for vehicle rating, in the case of log data can be seen that the average registration time vehicle information is reduced by 62% (from 15.17 min to 5.83 min..); in the case of the issuance of reports, which is also a fundamental issue as the Traffic Unit has the responsibility to respond to requests for information requiring the institutions or individuals, the time was reduced from 7.78 min. to 1.81 min, with which it can be said that the issuance of reports is 82% faster; and for the time of issue of duplicates can be seen that the average time of issuance of duplicates was reduced by 59% (from 7.67 min. 3.17 min.), after using Vehicular System Enabling.